Tectonostratigraphic evolution of the Dampier Sub-basin, Northern Carnarvon Basin, Western Australia - McHarg, Sam (Curtin University, 2018)
The complex interaction of Mesozoic fault orientation and basin scale features of the segmented Lewis Trough and en echelon Rankin Fault Zone suggest oblique reactivation of Carboniferous and Permian aged faults, somewhat at odds with the general perception of NW oriented extension associated with separation of Argoland from the NW shelf at this time. Mesozoic fault patterns observed suggest prolonged extension initiating in the Rhaetian, under an E-W oriented extensional regime.